Melatonin Molecular Biology, Clinical and Pharmaceutical Approaches - Manuela Drăgoi, Cristina; Crenguţa Nicolae, Alina (IntechOpen, 2018)
Melatonin, the pineal neurohormone, is a pleiotropic molecule acting in the center of the integrative molecular mechanisms of the organism, based on interconnections of the regulatory systems: neural, endocrine, immune, and genetic, conveying into the uniqueness of human architecture. This book provides a systematic and updated overview of melatonin biochemical mechanisms of action, pharmacological features, and clinical uses, clutching the subject with complete details of pharmaceutical formulations designed for different routes of administration and different health issues, aiming at optimal melatonin bioavailability when therapeutically delivered. The book addresses a broad range of audiences, from healthcare professionals, medically and pharmaceutically based, to highly profiled medical specialists and biomedical researchers, helping them to expand their knowledge of the physiological and pathological implications of melatonin and its metabolites.